THE RELATIONSHIP BETWEEN THE INTERPRETATION OF AL-IBRIZ BY K.H BISRI MUSTOFA AND THE INTERPRETATION OF AL-MUBARAK BY K.H TAUFIQUL HAKIM - Maulana Yusup; Masruchin Masruchin; Beko Hendro (Program Pascasarjana UIN Sumatera Utara, 2025)
In comprehending and elucidating the meaning of the Qur'an, an exegete cannot entirely detach themselves from the accumulated knowledge and interpretive methodologies that have previously evolved. Consequently, new interpretations consistently represent a dialogue with and an elaboration of the existing corpus of tafsir, rather than being solely a product of independent thought. Based on this premise, this research investigates the correlation between Tafsir Al-Ibriz and Tafsir Al-Mubarak. The study addresses two primary research questions. First, what is the correlation between Tafsir Al-Ibriz by K.H Bisri Mustofa and Tafsir Al-Mubarak by K.H Taufiqul Hakim. Second, in which section in the Tafsir Al-Mubarak are influenced by Tafsir Al-Ibriz. This study employs a qualitative methodology and is categorized as library reseacrh by utilizing Karl Mannheim's sociology of knowledge theory, specially focusing on ‘behavior and meaning' as its analitycal framework. The findings indicate a significant correlation between Tafsir Al-Ibriz and Tafsir Al-Mubarak. A prominent aspect of this correlation is the use of Javanese language in both exegitical works. This reflect the exegetes strategy to adapt the material, making it relevant and accesible to local audiences residing in their respective regions. Furthermore, in depth observation reveals that several sections of Tafsir Mubarak exhibit a strong dominance from Tafsir Al-Ibriz.